High resolution whole genome multilocus sequence typing (wgMLST) schemes for Salmonella enterica Weltevreden epidemiologic investigations - Pakpoom Tadee (2018)
© 2018, The Korean Society for Microbiology and Biotechnology. Non-typhoidal Salmonella is one of the main pathogens causing food-borne illness in humans, with up to 20% of cases resulting from consumption of pork products. Over the gastroenteritis signs, multidrug resistant Salmonella has arisen. In this study, pan-susceptible phenotypic strains of Salmonella enterica serotype Weltevreden recovered from pig production chain in Chiang Mai, Thailand during 2012−2014 were chosen for analysis. The aim of this study was to use whole genome sequencing (WGS) data with an emphasis on antimicrobial resistance gene investigation to assess their pathogenic potential and genetic diversity determination based on whole genome Multilocus Sequence Typing (wgMLST) to expand epidemiological knowledge and to provide additional guidance for disease control. Analyis using ResFinder 3.0 for WGS database tracing found that one of pan-susceptible phenotypic strain carried five classes of resistance genes: aminoglycoside, beta-lactam, phenicol, sulfonamide, and tetracycline associated genes. Twenty four and 36 loci differences were detected by core genome Multilocus Sequence Typing (cgMLST) and pan genome Multilocus Sequence Typing (pgMLST), respectively, in two matching strains (44/13 vs A543057 and A543056 vs 204/13) initially assigned by conventional MLST and Pulsed-field Gel Electrophoresis (PFGE). One hundread percent discriminant ability can be achieved using the wgMLST technique. WGS is currently the ultimate molecular technique for various in-depth studies. As the findings stated above, a new of “gold standard typing method era” for routine works in genome study is being set.